SAVING PUBLIC ACCESS. (American City & County, 2010)
The article discusses the foot traffic increase at the Public Library of Staunton, Virginia and the demand for free computing resources where only four of the eight personal computers (PCs) were functioning. The Windows software were subjected to computer hacking and downloading viruses. Kurt Plowman, the library's chief technology officer (CTO), began scouting for virtual desktops and centralized the computing power in the data center. The project won the city recognition during the annual Commonwealth of Virginia's Innovative Technology Symposium.